The VimL Primer : edit like a pro with Vim plugins and scripts - Klein, Benjamin; Rashid, Fahmida Y. (Pragmatic programmers., 2015)
Build on your editor's capabilities and tailor your editing experience with VimL, the powerful scripting language built into Vim. With VimL you can configure basic settings or add entirely new functionality. Use this quick and easy introduction to create your own Vim plugin while learning the concepts and syntax of VimL.